Dispersed ice of permafrost peatlands represents an important source of labile carboxylic acids, nutrients and metals - Kuzmina, Daria M.; Lim, Artem G.; Loiko, Sergey V.; Shefer, Nikita; Shirokova, Liudmila S.; Julien, Frédéric; Rols, Jean-Luc; Pokrovsky, Oleg S. (Geoderma)
Thawing of frozen organic and mineral soils and liberation of organic carbon (OC), macro- and micro-nutrients and trace elements from pore ice in high latitude regions represent a potentially important but poorly quantified retroactive linkage to climate warming. This is especially true for permafrost peatlands, occupying a sizable proportion of all permafrost territories and presenting a large and highly vulnerable stock of soil OC which can be subjected to fast thawing at currently circum-zero temperatures. The conventional method of assessing the labile water-soluble fraction of permafrost soils is aqueous extraction from dried soil. However, this technique does not allow collecting native ice present in soil pores and is therefore likely to underestimate or overestimate the pool of labile soil C and nutrients. Here, we present results of direct pore ice analyses performed on native peat cores from the western Siberia Lowland in comparison to the water extraction (10 and 100 gdry peat L-1) of soluble components from the same peat subjected to freeze drying. Aqueous leachates of permafrost peat from both thawed (0–45 cm) and frozen (45–130 cm) layers yielded high concentrations of DOC, nutrients, carboxylic acids and trace metals, comparable or higher to those in peat porewater and dispersed peat ice. We found strong (a factor of 3 to 30) enrichment in the frozen part of the core (below 45 cm, which is active layer depth) in dissolved OC, many carboxylates (acetate, formate, lactate, butyrate, propionate, pyruvate), inorganic nutrients (Si, P, N) and trace elements (Fe, Al, Mn, Zn, Sr and Ba). The dispersed ice which is present in peat below active layer represents highly labile reservoir of organic and inorganic nutrients which should be considered in permafrost thaw scenarios